Ultra‐broadband Polarisers Based on Metastable Free‐Standing Aligned Carbon Nanotube Membranes. Issue 10 (24th July 2014) - Cole, Matthew T.; Doherty, Matthew; Parmee, Richard; Dawson, Paul; Milne, William I.
<x xml:space="preserve">Abstract</x> A carbon nanotube free‐standing linearly dichroic polariser is developed using solid‐state extrusion. Membrane cohesion is experimentally and numerically demonstrated to derive from inter‐tube van der Waals interactions in this family of planar metastable morphologies, controlled by the chemical vapour deposition conditions. Ultra‐broadband polarisation (400 nm – 2.5 mm) is shown and corroborated by effective medium and full numerical simulations. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>